Which access matters? A comparative analysis of accessibility metrics and their impacts on commuting - Kapatsila, Bogdan; Negm, Hisham; El-Geneidy, Ahmed (Journal of Transport and Land Use, 2026)
Accessibility, a transport and land-use performance metric, is an umbrella term for several methodological approaches quantifying access to opportunities that can impact travel behavior. Some accessibility measures are easy to estimate and interpret, although they are based on restrictive assumptions, while others are more realistic but impose higher requirements for inputs, estimation, and interpretation. Selecting the measure of accessibility to incorporate in planning practice is a continuous challenge that professionals face. In this paper, we compare the strength of association between non-competitive and competition-based opportunity measures and the share of transit mode users at the Census Tract level of analysis in Toronto, Montreal, and Vancouver, Canada. Our findings confirm the positive association between all accessibility measures to jobs by public transit and transit mode share and identify that the simple cumulative opportunities calculated at the mean transit travel time of the region and gravity-based measures result in higher explanatory power compared to more complex competition-based measures, with a negligible level of difference between the former two. The insights from this paper can be of value to analysts and practitioners seeking to select accessibility measures that are representative of real conditions, easy to calculate and interpret, and with high predictive power of travel behavior in planning practice.